Patterns of land use and greenhouse gases emissions from Brazilian agriculture (1940-2014) - Dias, Lívia Cristina Pinto (2017)
Given the large size of Brazil, its enormous vegetation diversity and agriculture heterogeneity, the development of national agricultural and conservation policies requires an understanding of historical patterns of land use for the entire country. It is only through the lens of history that the current geographic trends in land use can be fully understood and accurate future projections made. This study analyzes the spatial patterns of the Brazilian agriculture between 1940 and 2014, with emphasis on land use and greenhouse gas emissions. I investigate the historical patterns of agricultural land use and greenhouse gases emissions in Brazil using a new historical-spatial database at spatial resolution of 30” (approximately 1 km x 1 km). Although the agriculture frontier is still expanding in the Amazon and Cerrado, rates are much lower than before, and throughout the eastern and southern part of the country, agricultural land use is actually decreasing. The production of soybean and maize increased due to increase in area and yields, but the production of sugarcane increased predominantly due to extensification. Pasturelands decreased in all regions analyzed, except in Amazonia, but the slow process of technology transference appears to be keeping the Brazilian stocking rate of cattle close to 1.0 head/ha, indicating an inefficient livestock system. Brazil is moving slowly towards a more intensive and sustainable agriculture. Until 1975, deforestation of the Atlantic Forest and Cerrado were the main sources of CO 2 emissions. After that, Amazonia took the first position as source of CO 2 emissions. Emissions from land use change in Atlantic Forest and Pampas decreased gradually after 1975 and these biomes become a sink of CO 2 since 1990. The total agricultural emissions are decreasing because the CO 2 emissions are decreasing and they are several times larger (in CO 2eq terms) than the CH 4 and N 2 O emissions. Brazil is heading towards the reduction of land use change emissions as proposed in the National Policy on Climate Change. About the Nationally Determined Contributions proposed in the 2015 Paris agreement, the past rates in forest restoration are more than sufficient to achieve the suggested measure proposed. The conclusion is that Brazil should be more audacious in its goals. My results provide one of the first comprehensive historical and geographically explicit overview of agricultural land use and greenhouse gases emissions in Brazil, providing clear insights to guide future territorial planning, sustainable agriculture, policy and decision-making.